Histone-like proteins in the purified Escherichia coli deoxyribonucleoprotein - Varshavsky, A. J. (1977)
Analysis of E.coli chromosomes isolated under conditions similar to those used for isolation of eukaryotic chromatin has shown that: 1) The proteins of highly purified E.coli deoxyribonucleoprotein are mainly in addition to RNA polymerase two specific histone-like proteins of apparent molecular weight of 17,000 and 9,000 (proteins 1 and 2, respectively). 2) Proteins 1 and 2 occur in approximately equal molar amounts in the isolated E.coli chromosome, and their relative content corresponds to one molecule of protein 1 plus one molecule of protein 2 per 150-200 base pairs of DNA. 3) There are no long stretches of naked DNA in the purified E.coli deoxyribonucleoprotein suggesting a fairly uniform distribution of the proteins 1 and 2 along DNA. 4) The protein 2 is apparently identical to the DNA-binding protein HU which was isolated previously /1/ from extracts of E.coli cells. 5) Digestion of the isolated E.coli chromosomes with staphylococcal nuclease proceeds through discrete deoxyribonucleoprotein intermediates (in particular, at ∼ 120 base pairs) which contain both proteins 1 and 2. However, since no repeating multimer structure was observed so far in nuclease digests of the E.coli chromosome, it seems premature to draw definite conclusions about possible similarities between the nucleosomal organization of the eukaryotic chromatin and the E.coli chromatin structure.